Impact of Process Control Devices on the Performance of Ultrafilter Membrane in Clean Water Production - Shahidul, Islam; Michael, Anggie Boniface; Rubiyah, Baini; Ahmad Adzlan Fadzli, Khairi; Hishammudin Afifi, Huspi (SEMARAK ILMU, 2024)
This paper aims to publish an experimental finding addressing ultrafilter membranes' higher energy consumption rate (UFM) in producing clean water. The novelty of the research published in this paper is to establish the contribution capability of process control devices (PCD) in reducing the energy consumption rate of UFM and the effect of PCD on the overall performance of UFM in producing clean water (SDG6). The novelty of the research published in this paper is to establish the contribution capability of PCD in reducing the energy consumption rate of UFM and the effect of PCD on the overall performance of UFM in producing clean water (SDG6). An experiment has been conducted with a UFM to answer the question. The UFM plant operated with and without process control devices to evaluate the impact of the process control devices on energy consumption rate [kW/m3] in producing clean water. Experiments revealed that process control devices are positively associated with energy consumption rate and contributed to reducing 44% of energy consumption in clean water production. This research disclosed that process control devices have contributed to an increase of 38% in the efficiency of the UFM in clean water production. Research outcomes have several implications in the water industry, engineering, and policy implementation domains relating to process control devices in water treatment. From our findings, further research should continue using process control devices for the water treatment plants to increase overall performance and contribute to achieving sustainable development goals (SDG).